Bribery in Public Procurement Methods, Actors and Counter-Measures (OECD Publishing, 2007)
Public works contracts mean big business. From road-building to high-tech communication infrastructure, public procurement averages 15% of GDP in OECD countries - substantially more in non-OECD economies - and it is a major factor in the world trade of goods and services. Given the growing complexity of bribe schemes in today's globalized markets, the problem is how to identify corruption in public procurement so governments can work toward effective prevention and apply sanctions if necessary. This report provides insights on all three fronts. Based on contributions from law enforcement and procurement specialists, the report describes how bribery is committed through the various stages of government purchasing; how bribery in public procurement is related to other crimes, such as fraud and money laundering; and how to prevent and sanction such crimes. The typical motivations and conduct of the various actors engaging in corruption are also highlighted, as well as ten case studies.--Publisher's description.